2013
DOI: 10.25011/cim.v36i4.19957
|View full text |Cite
|
Sign up to set email alerts
|

Levels of interleukin-33 and interleukin-6 in patients with acute coronary syndrome or stable angina

Abstract: Purpose: The purpose of this study was to investigate the levels of interleukin-33 (IL-33) and interleukin-6 (IL-6) in patients with acute coronary syndrome or stable angina. Methods: Serum IL-33 and IL-6 were measured with Enzyme Linked Immuosorbent Assay (ELISA) in patients with acute coronary syndrome (ACS, n = 40), and stable angina pectoris (SAP, n = 43). IL-33 and IL-6 were also determined in 30 healthy subjects (control group). Results: The serum level of IL-33 in the ACS group (78.60 ± 44.84 ng/L) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…20 This finding is in accordance with that of Liu et al who too had reported higher serum levels of IL-6 in patients with multivessel disease as compared with control group. 24 In our study, we observed a significant correlation with IL-6 levels and mGS, a finding reported by Tanidi et al 25 However, Mohktar et al found no association between IL-6 levels and the Gensini score. 20…”
Section: Discussionsupporting
confidence: 74%
“…20 This finding is in accordance with that of Liu et al who too had reported higher serum levels of IL-6 in patients with multivessel disease as compared with control group. 24 In our study, we observed a significant correlation with IL-6 levels and mGS, a finding reported by Tanidi et al 25 However, Mohktar et al found no association between IL-6 levels and the Gensini score. 20…”
Section: Discussionsupporting
confidence: 74%
“…It is also influential in the protection of cardiac muscle. In recent years, it has been the subject of much research that IL-33 and ST2 are associated with acute myocardial infarction, acute and chronic heart failure, aortic stenosis, and diastolic dysfunction, and interestingly, increased ST2 levels were generally found to be associated with poor outcomes [5153]. Moreover, it has been suggested that ST2 levels can be used as a cardiac biomarker [54].…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have demonstrated that the circulating levels of IL-33 and sST2 are associated with the severity of ACS patients, and may thus serve as potential biomarkers. The serum level of IL-33 is significantly lower in patients with ACS compared with stable angina pectoris patients and control individuals (31, 32). Similarly, another study showed that the circulating level of IL-33 is significantly lower in ACS patients than in patients with coronary artery disease (33).…”
Section: Cytokinesmentioning
confidence: 96%